2021
DOI: 10.1371/journal.pone.0245056
|View full text |Cite
|
Sign up to set email alerts
|

Attachment style, thought suppression, self-compassion and depression: Testing a serial mediation model

Abstract: Attachment anxiety has been consistently linked with increased vulnerability to depression, and hyperactivating emotion regulation strategies (e.g., rumination) have been shown to mediate this relationship. Investigations of mediators of the attachment avoidance to depression relationship have yielded inconsistent findings, and the nature of this relationship remains to be clarified. There is evidence to suggest that the constructs of thought suppression and self-compassion are associated with attachment avoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 73 publications
(72 reference statements)
3
13
0
Order By: Relevance
“…As discussed in the literature review, attachment avoidance could arguably lead to self-compassion if they also associate with positive views of the self (Wei et al, 2011). However, our finding that attachment avoidance negatively predicted self-compassion is more in line with similar investigations (Murray et al, 2021; Raque-Bogdan et al, 2016; Wei et al, 2011). Self-compassion and a positive view of one’s value or worth as a relationship partner (working model of self) are not identical constructs, but one could logically presume that such constructs would positively correlate.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As discussed in the literature review, attachment avoidance could arguably lead to self-compassion if they also associate with positive views of the self (Wei et al, 2011). However, our finding that attachment avoidance negatively predicted self-compassion is more in line with similar investigations (Murray et al, 2021; Raque-Bogdan et al, 2016; Wei et al, 2011). Self-compassion and a positive view of one’s value or worth as a relationship partner (working model of self) are not identical constructs, but one could logically presume that such constructs would positively correlate.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, those with a higher level of attachment anxiety appeared likely to be unkind to themselves (self-critical instead of self-kindness), exaggerate their negative experiences and feel uniquely victimized (isolation instead of common humanity), and feel overwhelmed by their painful thoughts and feelings (over-identification instead of mindfulness). That insecure attachments associate with less self-compassion has been noted by others (Murray et al, 2021;Neff & McGehee, 2010;Pepping et al, 2015;Raque-Bogdan et al, 2016;Wei et al, 2011). Similarly, others have found that selfcompassion tends to benefit divorce adjustment (Neff, 2003;Sbarra et al, 2012).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Third, we proposed the moderated serial mediation effects of brand authenticity and brand trust based on literature review and theorizations. In the empirical testing in Study 2, as we only collected cross-sectional data, we acknowledge that the temporal sequence of two mediators cannot be adequately tested in a cross-sectional design (Murray et al , 2021). Future research could collect panel data and further validate the temporal sequence of brand authenticity and brand trust as sequential mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Magee et al (2012) note that, if anything, clinical populations with high motivation to suppress intrusive thoughts, such as in obsessive-compulsive disorder or post-traumatic stress disorder, are slightly better at suppressing thoughts than non-clinical populations. There are, however, studies suggesting that thought suppression may exacerbate the effects of adverse life events, possibly resulting in increased risk of psychopathology (Murray et al, 2021), and there is evidence to suggest that thought suppression is related to symptom profiles and severity in eating disorders (Smith et al, 2019), and that it may mediate the relationship between emotional reactivity and non-suicidal self-injury (Najmi et al, 2007). In light of these and similar findings, Najmi and Wegner (2009) have suggested that thought suppression as a coping mechanism may serve to complicate and exacerbate certain types of psychopathology, and may induce long-term cognitive load.…”
Section: Consequences Of Thought Suppressionmentioning
confidence: 99%